The Approach The Approach of Religious Psychology in Islamic Religious Education Learning: Theoretical and Practical Perspectives: Pendekatan Psikologi Agama dalam Pembelajaran Pendidikan Agama Islam: Perspektif Teoritis dan Praktis - Nazila Mumtaza Zamhariroh; Achmad Zaini (STAI Terpadu Yogyakarta, 2025)
This study aims to examine the integration of religious psychology in the teaching of Islamic Religious Education, focusing on both theoretical and practical perspectives. The approach of religious psychology is used to enrich Islamic Religious Education by integrating the cognitive, emotional, and spiritual aspects of students, thus supporting the development of a deeper religious character. This research employs a literature review method, analyzing relevant literature such as books, journals, articles, and previous studies related to religious psychology, Islamic education, and the application of religious psychology in teaching. The results show that, from a theoretical perspective, the integration of religious psychology into Islamic Religious Education introduces psychological principles that can strengthen religious teaching. From a practical perspective, the application of religious psychology in Islamic Religious Education can enhance student motivation, strengthen religiosity, and shape religious attitudes and behaviors through methods such as spiritual reflection and moral discussions. However, this study also identifies challenges, such as the limited competence of teachers and the curriculum not fully supporting the optimal implementation of this approach. This research hopes to contribute to the development of a more holistic PAI curriculum and recommends teacher training to effectively implement the approach of religious psychology in teaching in madrasas and schools.